DEC2–E4BP4 Heterodimer Represses the Transcriptional Enhancer Activity of the EE Element in the Per2 Promoter - Tanoue, Shintaro; Fujimoto, Katsumi; Myung, Jihwan; Hatanaka, Fumiyuki; Kato, Yukio; Takumi, Toru (Frontiers in Neurology, 2015)
The circadian oscillation of clock gene expression in mammals is based on the interconnected transcriptional/translational feedback loops of Period (Per) and Bmal1. The Per feedback loop initiates transcription through direct binding of the BMAL1-CLOCK (NPAS2) heterodimer to the E-box of the Per2 promoter region. Negative feedback of PER protein on this promoter subsequently represses transcription. Other circadian transcription regulators, particularly E4BP4 and DEC2, regulate the amplitude and phase of Per2 expression rhythms. Moreover, a direct repeat of E-box-like (EE) elements in the Per2 promoter is required for its cell-autonomous circadian rhythm. However, the detailed mechanism for repression of the two core sequences of the EE element in the Per2 promoter region is unknown. Here we show that E4BP4 binds to the Per2 EE element with DEC2 to repress transcription and identify the DEC2-E4BP4 heterodimer as a key repressor of the tightly interlocked Per2 feedback loop in the mammalian circadian oscillator. Our results suggest an additional modulatory mechanism for tuning of the phase of cell-autonomous Per2 gene expression cycling.